2019
DOI: 10.1002/ceat.201800356
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Thermodynamic Modeling of Glycerin/Methanol/Organic Solvent Systems

Abstract: Glycerin is an important by-product in biodiesel production. To increase its quality to be suitable for use it in other operations, e.g., the pharmaceutical industry, it needs to be purified. Therefore, the purification of glycerin by liquid-liquid extraction of methanol using different solvents was investigated. It was shown that, in terms of separation, petroleum ether was more effective than toluene and toluene was more effective than n-butanol. In addition to the experimental investigations, the NRTL and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Applying the Othmer-Tobias and Hand thermodynamic models to the experimental data obtained for the systems analyzed proved to be reliable and consistent, since they exhibited correlation coefficients above 0.97 (Table 4). Mousavi et al [47] reported that the Othmer-Tobias and Hand correlations consistently represented the experimental equilibrium data of the systems containing glycerol + methanol + organic solvents.…”
Section: Thermodynamic Models 331 Othmer-tobias and Hand Correlationsmentioning
confidence: 78%
“…Applying the Othmer-Tobias and Hand thermodynamic models to the experimental data obtained for the systems analyzed proved to be reliable and consistent, since they exhibited correlation coefficients above 0.97 (Table 4). Mousavi et al [47] reported that the Othmer-Tobias and Hand correlations consistently represented the experimental equilibrium data of the systems containing glycerol + methanol + organic solvents.…”
Section: Thermodynamic Models 331 Othmer-tobias and Hand Correlationsmentioning
confidence: 78%
“…The numerous studies that have reported the LLE data of biofuels only investigated the separation processes in biodiesel production. Liquid–liquid equilibrium research aimed at proposing new fuel formulations is scarce in the literature. Thus, the aim of the present study focused on the use of biodiesel as an additive to stabilize alcohols in diesel blends: in other words, to investigate the miscibility of the ternary systems methanol + biodiesel + diesel, ethanol + biodiesel + diesel, and 1-butanol + biodiesel + diesel and propose new fuel formulations for diesel engines.…”
Section: Introductionmentioning
confidence: 99%